Surfactant modified graphene oxide laminates for filtration. (May 2017) - Lian, B.; Deng, J.; Leslie, G.; Bustamante, H.; Sahajwalla, V.; Nishina, Y.; Joshi, R.K.
Abstract: We have used a cationic surfactant cetyltrimethylammonium bromide (C16TAB) to increase the interlayer spacing between laminates in graphene oxide (GO) membranes for higher water flux. The addition of C16TAB to the GO membrane increased the permeability without compromising the ability to completely reject sucrose molecules. Species larger than sucrose can still permeate through modified GO membranes nearly with same rate as in the case of pure GO membranes. We speculate that interaction of C16TAB surfactant with sucrose molecules could be responsible for the selective rejection of sucrose. The selective rejection of sucrose, which is a common draw in forward osmosis (FO) process, suggests that surfactant modified GO membranes have the potential to improve the efficiency of the FO process. Graphical abstract: